VONNEGUT’S HUMANIST BELIEF AGAINST THE DEHUMANIZATION OF PEOPLE IN HIS THREE SELECTED SHORT STORIES - Rizka Khairina Johar (English Department, Faculty of Humanities, Andalas University, 2014)
In this study the author discusses several short story by American writer Kurt Vonnegut: